Coronary Wall Structural Changes in Patients With Kawasaki Disease: New Insights From Optical Coherence Tomography (OCT) - Audrey Dionne; Ragui Ibrahim; Catherine Gebhard; Mohamed Bakloul; Jean‐Bernard Selly; Mohamed Leye; Julie Déry; Chantale Lapierre; Patrice Girard; Anne Fournier; Nagib Dahdah (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2015)
Background Coronary artery aneurysms (CAA) are serious complications of Kawasaki disease (KD). Optical coherence tomography (OCT) is a high‐resolution intracoronary imaging modality that characterizes coronary artery wall structure. The purpose of this work was to describe CAA wall sequelae after KD. Methods and Results KD patients scheduled for routine coronary angiography underwent OCT imaging between March 2013 and August 2014. Subjects’ clinical courses, echocardiography, and coronary angiography examinations were reviewed retrospectively. OCT was performed in 18 patients aged 12.4±5.5 years, 9.0±5.1 years following onset of KD. Of those, 14 patients (77.7%) had a history of CAA (7 with giant CAA and 7 with regressed CAA at time of OCT). Intracoronary nitroglycerin was given to all patients (88.4±45.5 μg/m2). Mean radiation dose was 10.9±5.2 mGy/kg. One patient suffered from a transitory uneventful vasospasm at the site of a regressed CAA; otherwise no major procedural complications occurred. The most frequent abnormality observed on OCT was intimal hyperplasia (15 patients, 83.3%) seen at both aneurysmal sites and angiographically normal segments amounting to 390.8±166.0 μm for affected segments compared to 61.7±17 μm for unaffected segments (P<0.001). Disappearance of the media, and presence of fibrosis, calcifications, macrophage accumulation, neovascularization, and white thrombi were seen in 72.2%, 77.8%, 27.8%, 44.4%, and 33.3% of patients. Conclusions In this study, OCT proved safe and insightful in the setting of KD, with the potential to add diagnostic value in the assessment of coronary abnormalities in KD. The depicted coronary structural changes correspond to histological findings previously described in KD.